Extracellular Vesicle-Derived miR-105-5p Promotes Malignant Phenotypes of Esophageal Squamous Cell Carcinoma by Targeting SPARCL1 via FAK/AKT Signaling Pathway - He, Binjun; Zhang, Kang; Han, Xiaoliang; Su, Chao; Zhao, Jiaming; Wang, Guoxia; Wang, Guzong; Zhang, Liuya; Hu, Wenbin (Frontiers in Genetics, 2022)
Objective: Esophageal squamous cell carcinoma (ESCC) presents high morbidity and mortality. It was demonstrated that blood-derived vesicles can facilitate ESCC development and transmit regulating signals. However, the molecular mechanism of vesicle miRNA secreted by tumor cells affecting ESCC progression has not been explored. Methods: The mRNA-related signaling pathways and differentially expressed genes were screened out in TCGA dataset. The levels of miRNA-105-5p and SPARCL1 were determined by qRT-PCR. Protein level determination was processed using Western blot. The interaction between the two genes was verified with the dual-luciferase method. A transmission electron microscope was utilized to further identify extracellular vesicles (EVs), and co-culture assay was performed to validate the intake of EVs. In vitro experiments were conducted to evaluate cell function changes in ESCC. A mice tumor formation experiment was carried out to observe tumor growth in vivo. Results: MiRNA-105-5p expression was increased in ESCC, while SPARCL1 was less expressed. MiRNA-105-5p facilitated cell behaviors in ESCC through targeting SPARCL1 and regulating the focal adhesion kinase (FAK)/Akt signaling pathway. Blood-derived external vesicles containing miRNA-105-5p and EVs could be internalized by ESCC cells. Then, miRNA-105-5p could be transferred to ESCC cells to foster tumorigenesis as well as cell behaviors. Conclusion: EV-carried miRNA-105-5p entered ESCC cells and promoted tumor-relevant functions by mediating SPARCL1 and the FAK/Akt signaling pathway, which indicated that the treatment of ESCC via serum EVs might be a novel therapy and that miRNA-105-5p can be a molecular target for ESCC therapy.